Metastatic osteosarcoma: A case report on bilateral standard thoracotomy in a child. (2020) - Marzban-Rad, Saeid; Sattari, Parastesh; Azimi, Ghasem
Abstract: Introduction: Malignant cells from different organs after entering through peripheral blood circulation system trap into the first capillary bed in the lungs. Presentation of case: A 11-year-old boy with osteosarcoma in right leg was amputated. He had brain and lung metastasis. He underwent chemotherapy and resection of lung nodules with bilateral thoracotomy in two different phases. The patient was discharged in the healthy condition and clear chest radiography. Conclusion: The resection of the adenopathy at the mediastina and hilum pulmonis along with assessment of the hormonal receptors is recommended to determine the stage of the diseases. Highlights: For following up the patient with osteogenic sarcoma tumor, thorax spiral CT scan is suggested. Relapsing of the osteogenic sarcoma tumor, PET scan before the surgery is recommended. On which metastasectomy should not be performed if the metastases are in two different areas.